(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
To avoid the growth of COVID-19, universities in Delhi are stopped in March 2020. Several universities and teachers in Delhi return in September 2020, and instructors face significant ambiguity as a result of this unique circumstance. Ever since the start of the crisis, teachers have had psychological issues. They had to establish virtual learning during the lockdown, and so when schools reopen, they have expressed significant anxiety over the new, unexpected teaching environment. The purpose of this research is to assess the manifestations shown by teaching personnel in the Delhi NCR region during the reopening of schools. To do so, we gathered a sample of 100 instructors who completed an online questionnaire that evaluated stress, anxiety, and sadness using the DASS-21 (depression, anxiety, and stress scale) in addition to gathering socio-demographic data. According to the findings, a large majority of teachers had anxiety, sadness, and stress indicators. Gender, age, employment reliability, the degree of schooling at which they teach, and parental status all have an impact on this symptomatology. We believe that it is critical to protect teachers’ mental health to promote both classroom quality and patient psychological wellbeing.